Enantioselective Synthesis of Chiral 3‐Alkynyl‐3‐Hydroxyindolin‐ 2‐Ones by Zn/bis(Sulfonamide)‐Diamine Catalyzed Asymmetric Addition of Alkynes to Isatins. Issue 7 (1st June 2022) - Qu, Hongmin; Chen, Yu; Ceng, Xiangling; Tang, Pei; Wang, Huijing; Chen, Fener
Abstract: The catalytic enantioselective alkynylation of isatins, catalyzed by a Zn(OCOCF3 )2 /chiral bis(sulfonamide)‐diamine (BSDA) catalyst under mild condition, has been developed. The desired chiral 3‐alkynyl‐3‐hydroxy‐2‐oxindoles were obtained in moderate to excellent yields (up to 96%) and good to excellent enantioselectivites (up to 97% ee ). The reaction is broad in scope with respect to aryl‐substituted terminal alkynes and substituted isatins. Abstract : The catalytic enantioselective alkynylation of isatins, catalyzed by a Zn(OCOCF3 )2 /chiral bis(sulfonamide)‐diamine (BSDA) catalyst under mild condition, has been developed. The desired chiral 3‐alkynyl‐3‐hydroxy‐2‐oxindoles were obtained in moderate to excellent yields (up to 96%) and good to excellent enantioselectivites (up to 97% ee ). The reaction is broad in scope with respect to aryl‐substituted terminal alkynes and substituted isatins.